(untitled) (Altre Modernità, 2019)
In the tradition of the Argentine narrative that takes place in the Patagonian desert and narrates the conflicts of its past and present, the novels Sangre en el viento by Vicente Muleiro and El país del diablo by Perla Suez have been added in 2015. In the seminar New Violence / New Resistance, held at the University of Milan in March 2016, I presented a paper on the first one. The present work on the novel by Perla Suez is inserted in a larger study that, in addition to the Patagonian novels, contemplates the desert of the Puna of northwestern Argentina in the work of Hector Tizón. Its axis of analysis tries to answer the question about the modality of the new narrative strategies with which this story deals with the situation of the native peoples in this bloody region where since the conquest a violent and genocidal domination has been exercised over them whose tragic effects and Resistances still persist. From this perspective I will analyze the presence of a visual paradigm of cinema in its writing. Procedures such as the montage of scenes similar to the snapshot and the frames of the cinema constitute the constructive amalgam of the novel. For the story that narrates, located in the mid-nineteenth century, Suez has sought an original point of view and privileges the look of its protagonist, the young Lum, daughter of a "white" father and a Mapuche mother. It is she who exercises her resistance to the violence of the invading army.